Equine Influenza Virus—A Neglected, Reemergent Disease Threat - Sack, Alexandra (Emerg Infect Dis, 2019)
Equine influenza virus (EIV) is a common, highly contagious equid respiratory disease. Historically, EIV outbreaks have caused high levels of equine illness and economic damage. Outbreaks have occurred worldwide in the past decade. The risk for EIV infection is not limited to equids; dogs, cats, and humans are susceptible. In addition, equids are at risk from infection with avian influenza viruses, which can increase mortality rates. EIV is spread by direct and indirect contact, and recent epizootics also suggest wind-aided aerosol transmission. Increased international transport and commerce in horses, along with difficulties in controlling EIV with vaccination, could lead to emergent EIV strains and potential global spread. We review the history and epidemiology of EIV infections, describe neglected aspects of EIV surveillance, and discuss the potential for novel EIV strains to cause substantial disease burden and subsequent economic distress.